Analisa Pengaruh Variasi Temperatur dan Waktu Proses Elektroplating Krom Terhadap Daya Rekat dan Ketebalan Lapisan Pada Plastik ABS - Sri Bintang Abdul Rohman; Ratna Dewi Anjani; Najmudin Fauji (Peneliti.net, 2022)
Plastic is a material that can be used as a substitute for metal, this is because the material has advantages, such as light weight, corrosion resistance, and relatively cheap price. There are several types of plastics such as polyethylene, teflon, polysulfone, polypropylene, acrylonitrile-butadine-styrene (ABS), and so on (1). ABS plastic is the most widely used material for chrome plating. The butdine portion is evenly distributed in the acrylonitrile-styrene matrix, making ABS plastics have advantages such as metal being easier to stick to the substrate, low coefficient of thermal expansion, easy to print, and improved aesthetic appearance (2). Behind the advantages possessed, ABS plastic has weaknesses including hardness, less high friction resistance, and at low temperatures it is easy to damage. To overcome this deficiency, one of the methods used is by electroplating the krum, with variations in temperature, 40°C, 50°C and 60°C, as well as variations in lectroplating time of 10 minutes, 20 minutes, and 30 minutes. . The tests carried out are measuring the adhesive strength of the coating results and the thickness of the layer. The results showed that the temperature and time in the electroplating process affected the adhesion of the coating and the thickness of the layer, where the highest value of adhesion was the variation of time of 30 minutes and a temperature of 40°C with a value of 0.41 MPa and the lowest value of adhesion at a time variation. 10 minutes and a temperature of 60°C with a thickness value of 0.06 MPa. And the highest thickness value is with a time variation of 30 minutes and a temperature of 60°C with a thickness value of 35 m and the lowest thickness value at a time variation of 10 minutes and a temperature of 40°C, 50°C with a thickness value of 20 m